Dietary adherence and associated factors among hypertensive patients in governmental hospitals of Guji zone, Oromia, Ethiopia - Berhanu Abera; Tamiru Yazew; Elsabeth Legesse; Chala G. Kuyu (BMC, 2024)
Abstract Background The Dietary Approaches to Stop Hypertension (DASH) diet has been shown to reduce blood pressure in hypertensive adults, but there is limited information available on dietary adherence and related factors among hypertensive patients in the study area. Hence, the current study aimed to assess dietary adherence and associated factors among hypertensive patients aged greater than or equal to 18 years old in governmental hospitals of Guji zone, Oromia region, Ethiopia. Methods A facility-based cross-sectional study was conducted between June 5, 2023, and August 30, 2023. For this study, patients with a systolic blood pressure of 140 mmHg or higher and/or a diastolic blood pressure of 90 mmHg or higher on two separate occasions were classified as hypertensive. Thus, the study involved 399 hypertensive patients who were selected using systematic random sampling methods. The level of knowledge regarding hypertension was measured through the use of hypertension knowledge-level scale (HK-LS) questionnaires, while the reliability and validity of the questionnaire were assessed using the Cronbach's alpha test (α ≥ 0.70).The association between factors was analyzed using adjusted odds ratio (AOR) and a 95% confidence interval. Variables with p-values below 0.05 were considered statistically significant. Results Among the respondents, only 28.30% (CI: 23.9, 33) of participants were found to be adherent to the recommended diet. Factors like participation in nutritional education, level of knowledge, respondents' ages, and length of time since hypertension diagnosis showed a strong association with adherence to recommended dietary guidelines. Conclusions The research findings indicated that the level of compliance with the prescribed diet was generally subpar among individuals with hypertension in comparison to the Dietary Approaches to Stop Hypertension (DASH) diet recommendations. So, it is essential to offer hypertensive patients an education focused on health and nutrition in order to enhance their adherence to dietary guidelines and promote a healthier dietary routine. The results of this research will also be valuable in increasing awareness among policymakers and the general public about the dietary adherence and its associated factors, thus aiding in the development and execution of suitable interventions.